Worker-related ageism: A Systematic Review of Empirical Research - Cebola, Manuela (2021)
With the demographic and workforce ageing, ageism has been reflected in the work context. Ageism can be defined as stereotypes, prejudice and/or age-based discrimination. It is a form of devaluation and non-inclusion of workers, which materialises in a decent work deficit. It affects workers and organisations. The present literature review aims to provide a comprehensive and accurate picture of empirical research on worker-related ageism. We searched the word ageism in the title or abstract of articles indexed in the EBSCOhost and Web of Science. Fifty-eight peer-reviewed articles were retrieved (March 2020). Some of these articles report more than one empirical study. Thirty-two articles include quantitative design studies, 20 qualitative design, three mixed methods, two experimental and three instrument development and/or validation. The focus of the studies is mostly about negative ageism on older workers. The main findings present several facets of ageism and show different experiences, whether implicit or explicit. Ageism acts in a plurality of aspects, such as obstacles in the hiring process, employability and performance evaluation of older workers. We found research gaps such as determinants and interventions aiming at ageism prevention and proposed corresponding future research.